1998
DOI: 10.1111/0022-4146.00114
|View full text |Cite
|
Sign up to set email alerts
|

Do Exchange Rates and Foreign Incomes Matter for Exports at the State Level?

Abstract: At the national level, trade-weighted real exchange rates and foreign incomes significantly impact exports. At the subnational level, these variables are generally insignificant in the few studies that include them. We argue that the standard use of national trade weights in the construction of subnational trade-weighted averages of exchange rates and foreign incomes is inappropriate, and we then construct these variables using state-specific trade weights. In our panel data analysis of state-level manufacturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Turning to the trade variables, we included in the models both contemporaneous values and one-year lagged values for all four trade variables. One-year lags were included since prior research suggested that the effects of trade on regional economies may not necessarily be felt immediately because of the resistance of prices and wages to downward pressures, lags in new invest-ments, and other factors (Leichenko 2000;Cronovich and Gazel 1998). Our results for the trade exchange-rate variables are generally more consistent than for the tradeorientation variables.…”
Section: Results For All Statesmentioning
confidence: 51%
“…Turning to the trade variables, we included in the models both contemporaneous values and one-year lagged values for all four trade variables. One-year lags were included since prior research suggested that the effects of trade on regional economies may not necessarily be felt immediately because of the resistance of prices and wages to downward pressures, lags in new invest-ments, and other factors (Leichenko 2000;Cronovich and Gazel 1998). Our results for the trade exchange-rate variables are generally more consistent than for the tradeorientation variables.…”
Section: Results For All Statesmentioning
confidence: 51%
“…One approach uses regression analysis to estimate the extent to which foreign incomes affect state exports. These studies, exemplified by Erickson and Hayward (1991), Cronovich and Gazel (1998), and Coughlin and Wall (2003), find a strong, statistically significant relationship.…”
Section: Uneven Income Growthmentioning
confidence: 97%
“…Previous studies have found a considerable degree of variation in trade‐related effects across the U.S. Carlino, Cody, and Voith (1990) and Cronovich and Gazel (1998) find that the impacts of exchange rate movements vary in the U.S. at the state level. Moreover, Krugman (1991) and Shelburne and Bednarzik (1993) find that manufacturing sectors involved in trade tend to be more spatially concentrated than other, non‐traded sectors.…”
Section: Introductionmentioning
confidence: 97%